An evaluation analysis of students’ attitude towards physics learning at senior high school - Dwi Agus Kurniawan; Astalini Astalini; Deti Kurnia Sari (Graduate School, Universitas Negeri Yogyakarta, 2019)
This research is about students’ attitude analysis towards Physics learning conducted at senior high schools in Batanghari Regency. The purpose of this research is to know and evaluate students’ attitude toward Physics learning. This study is quantitative research employing Survey Research Design strengthened by the result of an interview to support quantitative data. This research involved 926 students of state senior high school in Batanghari. The instruments used by the researchers were in the form of questionnaires consisting of 54 items of statements by using 5-scale Likert. The results of this research show that students’ attitude is at good category and quite good based on the indicators used to investigate the attitude.